STRUCTURAL INTERCONNECTEDNESS OF THE GEOLOGICAL MEDIUM AND THE PHYSICAL MECHANISM OF FAULTING - Naymark A.A. (My University, 1996)
When predicting faulting in a known stress field or reconstructing the stressed state along systems of faults, it would be convenient to base the calculations on their simple geometric and kinematic relationships, which have been known for a long time from the mechanics of a continuous medium. However, the geological medium is not continuous but is constructed from weak points of various scales and various orientations relative to each other. The paper examines a number of theoretical models to describe faulting in the geological medium, with particular reference to shearing.